Negative electrode material for lithium ion secondary battery, negative electrode for lithium ion secondary battery, lithium ion secondary battery, and method of manufacturing the same
By using composite materials of microporous silicon particles and crushed graphite particles or graphene nanosheets in lithium-ion secondary batteries, the problem of battery cracks caused by changes in the volume of silicon-based materials is solved, and a higher charge and discharge capacity and cycle life are achieved.
Patent Information
- Application Number
- JP2023123194
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-07-28
AI Technical Summary
Among the existing negative electrode materials, silicon-based materials have problems of cracks and performance degradation due to volume changes in lithium-ion secondary batteries, especially due to the formation of the SEI layer and the reduction of conductivity.
Using a composite material containing microporous silicon particles and crushed graphite particles or graphene nanosheets, a conductive network is formed by coating the graphene layer on the surface of the silicon particles, reducing volume changes and improving conductivity.
The charging and discharge capacity and cycle life of lithium-ion secondary batteries are significantly improved, and the battery performance decline due to volume changes is reduced.
Smart Images

Figure 2025019540000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode material for a lithium ion secondary battery, a negative electrode for a lithium ion secondary battery, and methods for producing the same. [Background technology]
[0002] Lithium-ion secondary batteries have long been attracting attention from the perspective of meeting a wide range of energy demands, such as consumer batteries for mobile electronic devices, batteries for transportation such as electric cars, electric buses, and unmanned aerial vehicles (drones), and large batteries for large-scale energy storage systems. In the development of lithium-ion secondary batteries, active research is being conducted on the electrode materials and electrolytes that constitute them in order to achieve even larger capacity and higher energy density. One such research is the search for negative electrode materials using silicon particles. A negative electrode material made of silicon-based materials has a capacity of 4200 mAhg -1 This is said to have a theoretical capacity density of 372mAhg, which is the theoretical capacity density of the graphite anode that is currently most widely used. -1 For these reasons, silicon has been considered a promising anode material that can realize large-capacity lithium-ion secondary batteries.
[0003] However, there are technical challenges with anode materials made of silicon-based materials. The silicon contained in the anode of a lithium-ion secondary battery absorbs lithium ions during charging to become a lithium-silicon alloy represented by Li4Si, and releases lithium ions during discharging to return to silicon. During this process, silicon is said to undergo a volume change of more than 300%, and this large volume change can cause cracks and breakage in anodes containing silicon, significantly impairing the cycle characteristics of the lithium-ion secondary battery.
[0004] In order to solve such problems, it has been proposed to use porous silicon particles as the negative electrode material (see, for example, Patent Document 1). Because the silicon particles contained in the negative electrode are porous, the increase in volume accompanying the incorporation of lithium ions into the silicon particles is absorbed by filling the holes in the silicon particles, while the decrease in volume accompanying the release of lithium ions is compensated for by the regeneration of the filled holes. As a result, the change in volume of the negative electrode as a whole is suppressed, and cracks and breakage in the negative electrode are suppressed, so that the cycle characteristics of the lithium ion secondary battery can be prevented from being significantly impaired. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2018-120866 A Summary of the Invention [Problem to be solved by the invention]
[0006] Incidentally, a protective coating layer (SEI; solid electrolyte interface), which is a product of reduction and decomposition of the electrolyte, is usually formed on the surface of the negative electrode of a lithium-ion secondary battery. This is formed during initial charging of the lithium-ion secondary battery, and the presence of the electrically insulating SEI on the surface of the negative electrode suppresses further decomposition of the electrolyte. On the other hand, as described above, when the negative electrode cracks due to volume change, new silicon particles not covered by the SEI are exposed to the electrolyte, and an SEI layer is formed on the surface when the battery is charged. This crack formation and SEI layer formation are repeated, and an electrically insulating SEI layer penetrates between the silicon particles, reducing the electrical conductivity between these particles. This reduces the degree of uptake and release of lithium ions in the negative electrode, leading to a decrease in performance such as a decrease in the capacity and current of the secondary battery.
[0007] The present invention has been made in view of the above circumstances, and has an object to provide a negative electrode material for a lithium ion secondary battery that uses silicon having a large charging capacity and has good cycle characteristics, and a negative electrode for a lithium ion secondary battery using the same. [Means for solving the problem]
[0008] As a result of intensive research into solving the above problems, the present inventors have found that these problems can be solved by using a negative electrode material containing a composite of crushed graphite particles or graphene nanoplatelets having an average particle size of 0.1 μm to 30 μm and porous silicon particles, and have completed the present invention. Specifically, the present invention provides the following.
[0009] (1) The present invention provides a negative electrode material for a lithium ion secondary battery, comprising a composite of crushed graphite particles or graphene nanoplatelets having an average particle size of 0.1 μm to 30 μm and porous silicon particles.
[0010] (2) The present invention also relates to a negative electrode material for a lithium ion secondary battery according to item (1), wherein a mass ratio of the porous silicon particles (Si) to the crushed graphite particles or graphene nanoplatelets (G) is Si:G=5:1 to 5:5.
[0011] (3) The present invention also relates to a negative electrode material for a lithium ion secondary battery according to item (1) or (2), wherein the porous silicon particles are surface-coated with the crushed graphite particles or graphene nanoplatelets.
[0012] (4) The present invention also relates to a negative electrode material for a lithium ion secondary battery according to any one of (1) to (3), wherein the crushed graphite particles contain graphene flakes.
[0013] (5) The present invention also relates to a negative electrode for a lithium ion secondary battery, comprising the negative electrode material for a lithium ion secondary battery according to any one of items (1) to (4) on a graphene layer of a current collector having a graphene layer on a surface thereof.
[0014] (6) The present invention also relates to a lithium ion secondary battery comprising the negative electrode for lithium ion secondary batteries according to (5) above as a negative electrode.
[0015] (7) The present invention is also a method for producing a negative electrode material for a lithium ion secondary battery, comprising: a dispersing step of obtaining a dispersion through a step of crushing and / or dispersing the graphite or graphene nanoplatelets in the solvent by subjecting a mixture of the graphite or graphene nanoplatelets to a treatment using an external force; and a mixing step of mixing the dispersion obtained in the dispersing step with at least porous silicon particles, a binder, and water to prepare a slurry of a negative electrode active material mixture.
[0016] (8) The present invention also provides the method for producing a negative electrode material for a lithium ion secondary battery according to item (7), wherein the treatment by external force is ultrasonic treatment.
[0017] (9) The present invention also provides the method for producing a negative electrode material for a lithium ion secondary battery according to item (7) or (8), wherein the graphite is expanded graphite flakes.
[0018] (10) The present invention is also a method for producing a negative electrode material for a lithium ion secondary battery, comprising: a dispersing step of obtaining a dispersion in which the graphene nanoplatelets and the porous silicon particles are dispersed in the solvent by subjecting a mixture of the graphene nanoplatelets, the porous silicon particles, and a solvent to a treatment using an external force; and a mixing step of mixing the dispersion obtained in the dispersing step with at least a binder and water to prepare a slurry of a negative electrode active material mixture.
[0019] (11) The present invention also relates to a method for producing a negative electrode for a lithium ion secondary battery, comprising: a graphene layer-forming step of forming a single graphene layer on a surface of a current collector; and a coating step of coating the slurry obtained by the method according to any one of items (7) to (10) on the graphene layer of the current collector that has been subjected to the graphene layer-forming step, and drying the slurry. Effect of the Invention
[0020] According to the present invention, there are provided a negative electrode material for a lithium ion secondary battery which uses silicon having a large charging capacity and has good cycle characteristics, and a negative electrode for a lithium ion secondary battery using the same. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a plot of the charge retention versus the number of cycles for each negative electrode A (Si:G=5:1, 5:2, and 5:5) when negative electrode A, which does not have CVD single-layer graphene formed on the current collector, is used. [Diagram 2] FIG. 2 is a plot of the charge retention versus the number of cycles for each negative electrode A (Si:G=5:1, 5:2, and 5:5) when negative electrode A having CVD single-layer graphene formed on the current collector was used. [Diagram 3] FIG. 3 is a plot of the charge retention rate versus the number of cycles when negative electrode B (SiGNP) having CVD single-layer graphene formed on the current collector was used. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Hereinafter, an embodiment of the negative electrode material for lithium ion secondary batteries, an embodiment of the negative electrode for lithium ion secondary batteries, an embodiment of a lithium ion secondary battery, a first embodiment and a second embodiment of a method for producing a negative electrode material for lithium ion secondary batteries, and an embodiment of a method for producing a negative electrode for lithium ion secondary batteries of the present invention will be described. Note that the present invention is not limited to these embodiments or embodiments, and can be carried out by making appropriate modifications within the scope of the present invention.
[0023] <Anode materials for lithium-ion secondary batteries> First, one embodiment of the negative electrode material for lithium ion secondary batteries of the present invention will be described. The negative electrode material for lithium ion secondary batteries of the present invention (hereinafter, also simply referred to as the negative electrode material) is characterized by comprising a composite of crushed graphite particles or graphene nanoplatelets having an average particle size of 0.1 μm to 30 μm and porous silicon particles. The crushed graphite particles and graphene nanoplatelets have electrical conductivity, and the porous silicon particles, which are the negative electrode active material, are composited with such a conductive material, thereby realizing high electronic conduction between the negative electrode active material and the current collector, and also alleviating the volume expansion of silicon accompanying the storage of lithium ions. As a result, the negative electrode material of the present invention exhibits excellent specific charge / discharge capacity and good cycle characteristics. In particular, as graphite is crushed, a part of it may be converted into graphene flakes, which are two-dimensional materials, and the above-mentioned effects are more pronounced when the porous silicon particles, which are the negative electrode active material, are surrounded by the crushed graphite particles containing such graphene flakes or the graphene nanoplatelets, which are a type of graphene flakes.
[0024] The porous silicon particles contained in the negative electrode material of the present invention have a diameter of about 50 to 2000 nm, which is in the range of so-called nanoparticles to microparticles. The diameter is preferably 50 to 1000 nm.
[0025] The porous silicon particles have a plurality of surface pores. The diameter of the surface pores is preferably 10 to 100 nm, more preferably 10 to 80 nm, and even more preferably 10 to 70 nm. The porosity of the silicon particles is preferably about 30 to 60%, and more preferably about 30 to 50%. The porosity is a parameter that can be determined, for example, from BET nitrogen adsorption and density analysis, and indicates the ratio of the voids of the porous material to the total volume. By providing the porous silicon particles, which are the negative electrode material, with such surface pores, the occurrence of cracks due to volume changes accompanying charge and discharge can be suppressed in the negative electrode containing the particles, and the cycle characteristics of the secondary battery can be improved.
[0026] The porous silicon particles may be undoped silicon or doped silicon doped with impurities. In the case of doped silicon, the impurities for doping are preferably elements of group 13 or group 15. When the porous silicon particles contain such impurities, the conductivity of the silicon particles is improved, and the cycle characteristics are improved. Examples of group 13 elements include boron, etc. Examples of group 15 elements include phosphorus and arsenic, etc. Among these, phosphorus is preferred. The dopant concentration in the porous silicon particles is preferably 0.01 atom% to 3 atom%, more preferably 0.05 atom% to 1 atom%, and even more preferably 0.05 atom% to 0.3 atom%.
[0027] The crushed graphite particles are prepared by crushing graphite, and have an average particle size of 0.1 μm to 30 μm. The average particle size is preferably 0.1 μm to 10 μm, more preferably 0.1 μm to 5 μm, and even more preferably 0.5 to 3 μm. A method for crushing graphite is not particularly limited, but a preferable example is crushing graphite by applying ultrasonic vibration. As described above, the crushed graphite preferably contains graphene formed by exfoliation of graphite. The crushed graphite containing graphene pieces can be obtained, for example, by crushing commercially available expanded graphite flakes with ultrasonic vibration.
[0028] Graphene nanoplatelets are graphene flakes, and various grades are commercially available. Instead of crushed graphite particles, a composite may be formed with such graphene nanoplatelets. Although the thickness of graphene nanoplatelets is several nm, the size in the width direction, i.e., the average particle size, is on the order of μm, and graphene nanoplatelets with an average particle size of several tenths of μm to several tens of μm are commercially available. Therefore, even when graphene nanoplatelets are used, those with an average particle size of 0.1 μm to 30 μm are used as described above. The average particle size is preferably 0.1 μm to 10 μm, more preferably 0.1 μm to 5 μm, and even more preferably 0.5 to 3 μm.
[0029] The mass ratio of the porous silicon particles (Si) to the crushed graphite particles or graphene nanoplatelets (G) in the composite is preferably Si:G=5:1 to 5:5, and more preferably Si:G=5:2 to 5:5.
[0030] <Negative electrodes for lithium-ion secondary batteries> The present invention also includes a lithium ion secondary battery negative electrode (hereinafter, also simply referred to as a negative electrode) to which the lithium ion secondary battery negative electrode material using the negative electrode material of the present invention is applied. The negative electrode of the present invention is provided with the negative electrode material of the present invention on the graphene layer of a current collector having a graphene layer on its surface. By providing a graphene layer on the surface of the current collector, electronic conduction between the current collector and the negative electrode material containing crushed graphite particles or graphene nanoplatelets becomes smooth, and excellent specific charge / discharge capacity and good cycle characteristics are realized.
[0031] The current collector may be any current collector that has been used in the past for lithium ion secondary batteries, without any particular limitation, and examples of such current collectors include copper foil and aluminum foil.
[0032] The graphene layer provided on the surface of the current collector may be a single layer or multiple layers. A preferred method for forming the graphene layer on the surface of the current collector is to use a chemical vapor deposition method (CVD method) using ethanol, methane, or the like as a carbon source, but is not particularly limited thereto.
[0033] The negative electrode material, a composite of porous silicon particles and crushed graphite particles or graphene nanoplatelets, is mixed with a binder, a conductive additive, etc. and applied onto a current collector to form a negative electrode active material layer.
[0034] The binder may be any known binder without any particular limitation. Examples of such binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic acid, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc. The content of the binder in the negative electrode active material layer is preferably about 5% by mass to 30% by mass, more preferably about 5% by mass to 20% by mass. By setting the content of the binder within the above range, the negative electrode material, which is fine particles, can be stably held.
[0035] Examples of the conductive auxiliary include carbonaceous materials, metals, conductive ceramics, and the like. Examples of the carbonaceous materials include graphitized carbon, non-graphitized carbon, graphene-based carbon, and the like. Examples of the non-graphitized carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, and the like. Examples of the carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of the graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, and the like. Examples of the conductive auxiliary include powder and fiber. As the conductive auxiliary, one of these materials may be used alone, or two or more of them may be mixed and used. These materials may also be used in combination. For example, a material in which carbon black and CNT are combined may be used. Among these, carbon black is preferred from the viewpoint of electronic conductivity and coatability, and acetylene black is preferred among them. When a conductive auxiliary is used in the negative electrode active material layer, the proportion of the conductive auxiliary in the negative electrode active material layer is preferably 15 mass % or less, and more preferably 10 mass % or less.
[0036] <Lithium-ion secondary battery> The present invention also relates to a lithium ion secondary battery having the above-mentioned lithium ion secondary battery negative electrode of the present invention as a negative electrode. As already described, the lithium ion secondary battery negative electrode of the present invention provides excellent specific charge / discharge capacity and cycle characteristics, and therefore the lithium ion secondary battery of the present invention also exhibits excellent specific charge / discharge capacity and cycle characteristics.
[0037] <First embodiment of the method for producing a negative electrode material for a lithium ion secondary battery> Next, a first embodiment of the method for producing a negative electrode material for lithium ion secondary batteries of the present invention will be described. The method for producing a negative electrode material for lithium ion secondary batteries of this embodiment includes a dispersion step of crushing and / or dispersing a mixture of graphite or graphene nanoplatelets and a solvent by treating the mixture with an external force to obtain a dispersion, and a mixing step of mixing the dispersion obtained in the dispersion step with porous silicon particles, a binder, and water to prepare a slurry of a negative electrode active material mixture. That is, the negative electrode material for lithium ion secondary batteries obtained by this manufacturing method is a slurry of a negative electrode active material mixture containing the negative electrode material for lithium ion secondary batteries of the present invention. Each step will be described below.
[0038] [Dispersion process] First, the dispersion process will be described. The dispersion process is a process of crushing and / or dispersing the graphite or graphene nanoplatelets in the solvent by subjecting a mixture of the graphite or graphene nanoplatelets and the solvent to a treatment using an external force to obtain a dispersion liquid. In the following description, "graphite or graphene nanoplatelets" will be abbreviated as "graphite, etc.", and "crushed graphite particles or graphene nanoplatelets" will be abbreviated as "crushed graphite particles, etc." as appropriate.
[0039] As the graphite, various graphites can be used without any particular restrictions. As such graphite, expanded graphite flakes can be preferably used. Graphite (black lead) has a crystal structure in which turtle-shell-like layers are bonded to each other by weak van der Waals forces, and other elements or compounds can be inserted (intercalated) between these layers. Expanded graphite flakes are carbon materials in which substances such as sulfates are inserted between the layers of scaly graphite, and have the property that the layers peel off and graphite pieces are easily generated when subjected to an external force. As already mentioned, in the negative electrode material of the present invention, high electronic conduction is realized between the negative electrode active material and the current collector by surrounding the porous silicon particles with crushed graphite particles, and the volume expansion of silicon accompanying the storage of lithium ions is mitigated, but these effects are further enhanced by the crushed graphite particles containing graphene flakes. For this reason, expanded graphite flakes are preferably used as the graphite raw material. Various types of such expanded graphite flakes are commercially available, and these commercially available products may be obtained and used.
[0040] Graphene nanoplatelets are flakes of graphene and are commercially available in various grades. Unlike crushed graphite, graphene nanoplatelets are themselves flakes of graphene and can effectively surround porous silicon. Therefore, it is expected that the above effects can be obtained at a higher level when graphene nanoplatelets are used than when crushed graphite is used.
[0041] When graphite is mixed with a solvent and an external force is applied to the graphite, the graphite is dispersed in the solvent and converted into crushed graphite particles. Examples of the solvent include various solvents such as hydrocarbons, alcohols, water, ethers, and N-methyl-2-pyrrolidone. Among these, from the viewpoint of promoting the dispersion of graphite and obtaining crushed graphite particles with a finer particle size, a solvent having a certain degree of viscosity and polarity is preferable, and N-methyl-2-pyrrolidone is a preferable example of such a solvent. Note that graphene nanoplatelets may be used instead of graphite. Although graphene nanoplatelets are themselves graphene pieces with a fine particle size, they are usually in an aggregated state, so when using them, they need to be mixed with a solvent and dispersed in the solvent by applying an external force in the same manner as the above graphite. The preferable solvent in this case is the same as that for the above graphite.
[0042] The amount of the solvent is not particularly limited as long as it is sufficient to disperse the graphite, etc., to be treated. One example of the amount of the solvent is about 100 mL per 2 g of graphite, etc.
[0043] The mixture of the graphite or the like to be treated and the solvent is subjected to a treatment using an external force. As described above, this treatment using an external force produces a dispersion in which the crushed graphite particles or the like are dispersed in the solvent. Examples of such external forces include ultrasonic vibration, kneading, stirring with a stirrer, and the like. Of these, the treatment using ultrasonic vibration is preferred, and a preferred example of a means for such treatment using ultrasonic vibration is treatment with a commercially available ultrasonic homogenizer.
[0044] When treating with an ultrasonic homogenizer, a mixture of graphite or the like and a solvent is placed in an appropriate container, and the mixture is crushed by contacting the crushing horn of a commercially available ultrasonic homogenizer device with the mixture. The conditions for crushing with an ultrasonic homogenizer include a maximum amplitude of 60%, an oscillation time (ON / OFF) of 10 seconds / 5 seconds, and a processing time (cumulative oscillation ON time) of about 2 hours, but these conditions can be set appropriately. When crushing with ultrasonic vibration, it is preferable to cool the container while performing the treatment so that the liquid temperature of the mixture does not rise too much.
[0045] The dispersion liquid in which the crushed graphite particles, etc. are dispersed in the solvent by the treatment using an external force is subjected to a mixing step. The crushed graphite particles, etc. may be collected from the dispersion liquid by filtration, heated and dried, and then mixed with the solvent, and the treatment using an external force may be performed again. By repeating such treatment, it is possible to obtain crushed graphite particles, etc. having a finer particle size, and by using such crushed graphite particles, it is possible to obtain a negative electrode material exhibiting excellent properties.
[0046] The average particle size of the crushed graphite in the dispersion is preferably 0.1 μm to 30 μm. The average particle size is more preferably 0.1 μm to 10 μm, even more preferably 0.1 μm to 5 μm, and particularly preferably 0.5 to 3 μm. The average particle size of the graphene nanoplatelets in the dispersion is preferably 0.1 μm to 30 μm. The average particle size is more preferably 0.1 μm to 10 μm, even more preferably 0.1 μm to 5 μm, and particularly preferably 0.5 to 3 μm.
[0047] [Mixing process] The mixing step is a step of preparing a slurry of a negative electrode active material mixture by mixing at least the dispersion liquid obtained in the dispersing step, porous silicon particles, a binder, and water.
[0048] Porous silicon particles are fine silicon particles having a plurality of surface pores. As already mentioned, the porous silicon particles have a diameter of about 50 to 2000 nm, and belong to the range of so-called nanoparticles to microparticles. The diameter is preferably 50 to 1000 nm. The diameter of the surface pores is preferably 10 to 100 nm, more preferably 10 to 80 nm, and even more preferably 10 to 70 nm. The porosity of the silicon particles is preferably about 30 to 60%, and more preferably about 30 to 50%.
[0049] There is no particular limitation on the means for obtaining porous silicon particles. One example of such a means is a surface porosity treatment of silicon particles by a metal-assisted chemical etching method. In the metal-assisted chemical etching method, silicon particles are etched by coexisting transition metal ions and hydrofluoric acid in an etching solution, and surface pores are formed on the silicon particle surface through the following process. Next, an example of a porosity treatment of silicon particles by a metal-assisted chemical etching method will be described.
[0050] In the metal-assisted chemical etching method, silicon particles are first immersed in a solution containing transition metal ions and hydrofluoric acid. The hydrofluoric acid dissolves and removes the oxide film (SiO2) covering the surface of the silicon particles. This exposes silicon (Si) on the surface of the silicon particles, and this silicon comes into contact with the transition metal ions in the solution. Then, the electrons contained in the silicon are transferred to the transition metal ions, and the transition metal ions become transition metal particle nuclei on the spot and attach to the silicon particle surface, while at the contact points between the transition metal particle nuclei and the silicon particles, the silicon loses electrons and is locally oxidized. The locally oxidized silicon is removed by the hydrofluoric acid contained in the solution, and then is further oxidized by the transition metal ions at the contact points, and the transition metal particle nuclei grow. This reaction is repeated, and the transition metal particles are inserted into the silicon particles as if they are digging into the silicon surface, forming holes at those points. This reaction occurs at various points on the silicon particle surface, forming multiple surface holes on the silicon particle surface.
[0051] As the silicon particles to be used as the raw material, commercially available silicon particles may be used, or silicon sludge, which is silicon cutting powder generated when cutting a silicon wafer, may be used. The silicon particles may be doped silicon doped with impurities, or may be undoped. As already mentioned, when making doped silicon, the impurities for doping are preferably elements of group 13 or group 15. Examples of group 13 elements include boron, etc. Examples of group 15 elements include phosphorus, arsenic, etc. Among these, phosphorus is preferably used. The dopant concentration in the silicon particles is preferably 0.01 atom% to 3 atom%, more preferably 0.05 atom% to 1 atom%, and even more preferably 0.05 atom% to 0.3 atom%. When making the porous silicon particles into doped silicon, the porous silicon particles may be obtained from doped silicon as described above, or the porous silicon particles may be obtained from undoped silicon as a raw material and then doped with impurities.
[0052] The metal-assisted chemical etching method for making silicon particles porous includes a first etching substep in which the silicon particles are immersed in a solution containing hydrofluoric acid and transition metal ions to precipitate transition metal particles on the surfaces of the silicon particles, and the surfaces of the silicon particles whose contact parts with the transition metal particles have been oxidized as a result of the precipitation are etched with hydrofluoric acid, a second etching substep in which an oxidizing agent is added to the mixed solution obtained in the first etching step and reacted while being mixed, and an acid treatment substep in which the silicon particles obtained in the second etching step are treated with acid to remove the transition metal particles from the silicon particles. These three substeps are described below.
[0053] First etching sub-process The first etching sub-process is a process in which silicon particles are immersed in a solution containing hydrofluoric acid and transition metal ions to precipitate transition metal particles on the surfaces of the silicon particles, and the surfaces of the silicon particles, which have been oxidized at the contact points with the transition metal particles due to the precipitation, are etched with hydrofluoric acid.
[0054] When carrying out this sub-step, silicon particles are added to an appropriate amount of water to form a mixed solution, and hydrofluoric acid and transition metal ions are added to this mixed solution. The amount of the mixed solution in this case can be about 150 mL per 1 g of silicon particles. The order of addition of hydrofluoric acid and transition metal ions is not particularly limited and may be any order.
[0055] The transition metals include copper, silver, gold, iron, etc., and among these, silver is preferred. These transition metals are added to the mixed solution in the form of a transition metal salt, and become transition metal ions. Examples of such transition metal salts include hydrochlorides, nitrates, sulfates, etc., and among these, nitrates are preferred.
[0056] The concentration of the transition metal ions in the mixed solution is preferably 0.7 mmol / L to 30 mmol / L, more preferably 5 mmol / L to 25 mmol / L, and most preferably about 20 mmol / L.
[0057] The concentration of hydrofluoric acid in the mixed liquid is preferably about 2 mol / L to 4 mol / L, and more preferably about 3 mol / L.
[0058] The mixed solution to which the transition metal ions and hydrofluoric acid have been added is appropriately stirred at room temperature (approximately 15°C to 30°C) to allow the etching reaction to proceed. The stirring time is, for example, approximately 1 minute, but is not particularly limited. The resulting mixed solution is subjected to the second etching sub-step.
[0059] Second etching sub-process The second etching sub-step is a step of adding an oxidizing agent to the mixed solution that has been subjected to the first etching sub-step, and reacting them while mixing them. As already mentioned, in the first etching sub-step, the silicon particles are locally oxidized by the exchange of electrons between the transition metal ions and the silicon particles, and then the oxidized silicon is dissolved by hydrofluoric acid, causing local etching. However, as the transition metal particles are generated on the surface of the silicon particles, the supply of electrons gradually becomes saturated, making it difficult to locally etch the silicon particles, and it becomes impossible to increase the pore depth required for porosity. Therefore, in the second etching sub-step, an oxidizing agent is additionally added to the mixed solution. As a result, the electrons in the transition metal particles are taken away by the hydrogen peroxide, and local etching in the depth direction inside the silicon particles is promoted.
[0060] The oxidizing agent is not particularly limited, but preferably includes hydrogen peroxide. When hydrogen peroxide is used as the oxidizing agent, the concentration of hydrogen peroxide in the mixed liquid is preferably about 0.03 mol / L to 0.09 mol / L, and more preferably about 0.06 mol / L.
[0061] The mixture containing the hydrogen peroxide solution is stirred while being heated to about 50° C. During this time, the surfaces of the silicon particles are etched to form surface pores. The reaction time is preferably about 10 to 90 minutes, and more preferably about 30 to 60 minutes.
[0062] After the above reaction, an appropriate amount of water is added to the mixture to reduce the concentration of hydrofluoric acid and hydrogen peroxide, thereby stopping the etching reaction. The silicon particles contained in the mixture are then subjected to an acid treatment sub-step.
[0063] · Acid treatment sub-process The acid treatment sub-step is a step of treating the silicon particles that have been subjected to the second etching sub-step with acid, thereby removing the transition metal particles from the silicon particles.
[0064] In this sub-step, the silicon particles that have been subjected to the second etching sub-step are subjected to an acid treatment to remove the transition metal particles. Specifically, the silicon particles contained in the mixed liquid are put into the acid aqueous solution as the mixed liquid or after being filtered out from the mixed liquid, and immersed therein. As a result, the transition metal particles are transferred from the silicon particles to the acid aqueous solution. The acid aqueous solution used in this step is preferably concentrated nitric acid, and the treatment method in this step is to immerse the filtered silicon particles in the acid aqueous solution for about 20 minutes.
[0065] The silicon particles that have been subjected to the acid treatment in this sub-step have a plurality of surface pores formed on their surfaces, and the porous silicon particles thus obtained can be used in the mixing step of the manufacturing method of the present invention.
[0066] The binder may be any known binder without any particular limitation. Examples of such binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic acid, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc. The content of the binder in the slurry is preferably about 5% by mass to 30% by mass, more preferably about 5% by mass to 20% by mass, as a dry mass.
[0067] In addition, it is preferable to add a conductive auxiliary to the slurry. The conductive auxiliary may be any known one without any particular limitation. Such conductive auxiliary may be a carbonaceous material, a metal, a conductive ceramic, or the like. Examples of carbonaceous materials include graphitized carbon, non-graphitized carbon, graphene-based carbon, and the like. Examples of non-graphitized carbon include carbon nanofiber, pitch-based carbon fiber, carbon black, and the like. Examples of carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of graphene-based carbon include graphene, carbon nanotube (CNT), fullerene, and the like. Examples of the conductive auxiliary may include powder, fibrous, and the like. As the conductive auxiliary, one of these materials may be used alone, or two or more of them may be mixed and used. In addition, these materials may be used in a composite form. For example, a material in which carbon black and CNT are composited may be used. Among these, carbon black is preferable from the viewpoint of electronic conductivity and coatability, and acetylene black is preferable among them. When a conductive auxiliary is used, the content of the conductive auxiliary in the slurry is preferably 15% by mass or less, and more preferably 10% by mass or less, in terms of dry mass.
[0068] The dispersion liquid containing the crushed graphite particles and the like obtained in the dispersion process, the porous silicon particles, the binder, water, and, if necessary, the conductive auxiliary are mixed to prepare a slurry of the negative electrode active material mixture. Prior to this mixing, it is preferable to mix the dispersion liquid obtained in the dispersion process with the porous silicon particles, perform ultrasonic treatment, and collect the particles by filtration, and then dry them to form a composite. As already mentioned, the mass ratio of the porous silicon particles (Si) to the crushed graphite particles and the like (G) in this composite is preferably Si:G=5:1 to 5:5, and more preferably Si:G=5:2 to 5:5.
[0069] The slurry thus prepared is a negative electrode active material mixture for a lithium ion secondary battery, and the negative electrode for a lithium ion secondary battery can be prepared by applying the slurry to a substrate that serves as a current collector. Thus, the slurry obtained by the production method of the present invention can be preferably used as a negative electrode material for a lithium ion secondary battery.
[0070] Next, a second embodiment of the method for producing a negative electrode material for a lithium ion secondary battery of the present invention will be described. The method for producing a negative electrode material for a lithium ion secondary battery of this embodiment includes a dispersion step of obtaining a dispersion liquid in which the graphene nanoplatelets and the porous silicon particles are dispersed in the solvent by subjecting a mixture of the graphene nanoplatelets, the porous silicon particles, and a solvent to a treatment using an external force, and a mixing step of mixing the dispersion liquid obtained in the dispersion step with at least a binder and water to prepare a slurry of a negative electrode active material mixture.
[0071] In the manufacturing method of the first embodiment, a mixture of graphite or graphene nanoplatelets and a solvent is subjected to a treatment by external force to prepare a dispersion, but in the manufacturing method of the present embodiment, a mixture of graphene nanoplatelets, porous silicon particles, and a solvent is subjected to a treatment by external force to prepare a dispersion. That is, this embodiment differs from the first embodiment in that porous silicon particles are present in the dispersion step, and a dispersion containing the porous silicon particles and the graphene nanoplatelets is prepared. Therefore, in this embodiment, a slurry is prepared without adding porous silicon particles in the subsequent mixing step. Since the other points are the same as those of the first embodiment, the description here is omitted.
[0072] The average particle size of the graphene nanoplatelets in the dispersion is preferably 0.1 μm to 30 μm, more preferably 0.1 μm to 10 μm, further preferably 0.1 μm to 5 μm, and particularly preferably 0.5 to 3 μm.
[0073] <Method of manufacturing negative electrode for lithium ion secondary battery> The present invention also relates to a method for producing a negative electrode for a lithium ion secondary battery using a slurry that is a mixture of negative electrode active materials obtained by the method for producing a negative electrode material for a lithium ion secondary battery of the present invention. The method for producing a negative electrode for a lithium ion secondary battery of the present invention is characterized by comprising a graphene layer forming step of forming a single graphene layer on the surface of a current collector, and a coating step of coating the graphene layer of the current collector that has been subjected to the graphene layer forming step with the slurry obtained by the above method and drying it. As described in the description of the negative electrode for a lithium ion secondary battery of the present invention, by providing a graphene layer on the surface of the current collector, electronic conduction between the negative electrode material containing crushed graphite particles and the current collector becomes smooth, and excellent specific charge / discharge capacity and cycle characteristics are realized. The method for producing a negative electrode for a lithium ion secondary battery of the present invention is for preparing such a negative electrode. Each step will be described below.
[0074] [Graphene layer formation process] The graphene layer forming step is a step of forming a single graphene layer on the surface of the current collector. Instead of performing this step, a metal foil having a graphene layer formed on its surface may be obtained and used. In this case, this step may be considered as having been performed, and the process may proceed to the coating step described below.
[0075] The current collector may be any current collector that has been used in the past for lithium ion secondary batteries, without any particular limitation, and examples of such current collectors include copper foil and aluminum foil.
[0076] The graphene layer provided on the surface of the current collector may be a single layer or multiple layers. A preferred method for forming the graphene layer on the surface of the current collector is to use a chemical vapor deposition method (CVD method) using ethanol, methane, or the like as a carbon source, but is not particularly limited thereto.
[0077] The current collector having the graphene layer formed on its surface is subjected to a coating step.
[0078] [Coating process] The coating step is a step of coating the slurry obtained by the above-mentioned method for producing a negative electrode material for a lithium ion secondary battery onto the graphene layer of the current collector that has been subjected to the graphene layer formation step, and drying the coated graphene layer.
[0079] The slurry may be applied by any known method without any particular limitation. Through this process, a negative electrode active material layer is formed on the surface of the graphene layer, and the negative electrode for a lithium ion secondary battery of the present invention is obtained. EXAMPLES
[0080] The present invention will be described in more detail below by showing examples, but the present invention is not limited to the following examples in any way.
[0081] [Preparation of porous silicon particles] Porous silicon particles were prepared using industrial waste silicon sludge (obtained from Japan NER Co., Ltd.) with an average diameter of approximately 530 nm as the raw material. First, the silicon sludge was heat-treated at 600°C for 30 minutes in an argon atmosphere to graphitize the insulating carbon-based organic matter contained in the silicon sludge, thereby obtaining heat-treated silicon particles.
[0082] 1.2 g of heat-treated silicon particles were cleaned by ultrasonication in acetone and then in ethanol for 10 min each, then washed for 60 min in piranha solution, a 3:1 (v / v) mixture of concentrated sulfuric acid and hydrogen peroxide heated to 110 °C, and then washed with deionized water.
[0083] Next, the silicon particles were made porous by the metal-assisted chemical etching method in the following procedure. First, 1 g of silicon particles that had been washed as described above was added to deionized water, and the silicon particles were uniformly dispersed in the deionized water by treating them with an ultrasonic homogenizer for 5 minutes. Then, an etching solution consisting of 3.0 M hydrofluoric acid and 0.02 M silver nitrate was added to this dispersion, and silver nanoparticles were precipitated on the surface of the silicon particles by stirring at 50 rpm for 1 minute using a stirrer. The amount of the reaction solution at this time was 150 mL. The silicon particles were made porous by adding 0.06 M hydrogen peroxide to this dispersion containing hydrofluoric acid and reacting it for 60 minutes at a stirring speed of 50 rpm while heating it to 50 ° C. Then, the silicon particles were washed with deionized water, washed with a concentrated nitric acid solution for 40 minutes to completely remove the residual silver nanoparticles present inside the pores, and finally washed with deionized water to obtain porous silicon particles. The average pore diameter of the surface pores of the porous silicon particles measured with a specific surface area / pore distribution measuring device (Microtrack Bell Co., Ltd., product name BELSORP) was 13.985 nm. The specific surface area of the porous silicon particles was 89.543 m 2 / g, and the total pore volume is 0.3131 cm 3 / g and the pore volume is 0.2972 cm 3 / g. These operations were repeated to obtain the amount of porous silicon particles required for the preparation described below.
[0084] [Preparation of crushed graphite particle dispersion] 2.0 g of expanded graphite flakes (manufactured by Ito Graphite Industries Co., Ltd., product name EC10) was added to N-methyl-2-pyrrolidone (100 mL) and treated with an ultrasonic homogenizer. The conditions of the ultrasonic homogenizer treatment were Amplitude: 60%, Pulse ON: 10.0 seconds, Pulse OFF: 5.0 seconds, and the total pulse ON time was 2 hours. Next, the crushed graphite particles were temporarily collected by vacuum filtration, and the particles were thoroughly dried at 150°C, and then added to fresh N-methyl-2-pyrrolidone (100 mL) and treated with an ultrasonic homogenizer. The conditions of the ultrasonic homogenizer treatment at this time were the same as those described above. Next, the crushed graphite particles were temporarily collected by vacuum filtration, and the particles were thoroughly dried at 150°C.
[0085] 0.8 g of the obtained dried particles were added to fresh N-methyl-2-pyrrolidone (40 mL) and treated a third time with the ultrasonic homogenizer. The conditions for the ultrasonic homogenizer treatment at this time were Amplitude: 60%, Pulse ON: 10.0 seconds, Pulse OFF: 5.0 seconds, and the total pulse ON time was 6 hours. The dispersion liquid that had undergone this treatment was used as a crushed graphite particle dispersion liquid. When the obtained crushed graphite particles were observed with a scanning electron microscope, they were found to contain graphene flakes and the calculated average particle size was 0.93 μm.
[0086] [Preparation of porous silicon particles / crushed graphite particle composite (Si / G composite) 1] 1.2 g of the porous silicon particles obtained by the above procedure was added to 12 mL of the crushed graphite particle dispersion (corresponding to 0.24 g of crushed graphite particles) obtained by the above procedure and treated with an ultrasonic homogenizer. The mass ratio of Si:G (porous silicon particles: crushed graphite particles) at this time was 5:1. The conditions of the ultrasonic homogenizer treatment were Amplitude: 30%, Pulse ON: 10.0 seconds, Pulse OFF: 5.0 seconds, and the total pulse ON time was 30 minutes. After stirring the treated dispersion for 30 minutes with a high-shear mixer (22,000 rpm), the Si / G complex was collected by vacuum filtration and thoroughly dried at 150 °C to obtain a Si / G complex (Si:G = 5:1).
[0087] [Preparation of porous silicon particles / crushed graphite particle composite (Si / G composite) 2] A Si / G composite (Si:G=5:2) was obtained in the same manner as above, except that the amount of the crushed graphite particle dispersion was 25 mL (corresponding to 0.5 g of crushed graphite particles) and the amount of the porous silicon particles was 1.25 g.
[0088] [Preparation of porous silicon particles / crushed graphite particle composite (Si / G composite) 3] A Si / G composite (Si:G=5:5) was obtained in the same manner as above, except that the amount of the crushed graphite particle dispersion was 32 mL (corresponding to 0.64 g of crushed graphite particles) and the amount of the porous silicon particles was 0.64 g.
[0089] [Preparation of negative electrode active material mixture slurry 1] For each of the three types of Si / G composites (Si:G=5:1, 5:2, and 5:5), the raw materials were mixed in the ratio shown in Table 1 to prepare anode active material mixture slurry. In Table 1, "carbon black" is conductive carbon black (product name SuperP) manufactured by MTI. The procedure for preparing the anode active material mixture slurry was as follows. First, polyacrylic acid was added to pure water and stirred for 10 minutes, and conductive carbon black was added to the obtained solution and stirred for another 10 minutes to obtain a mixed solution. The Si / G composite obtained by the above procedure was added to the obtained mixed solution and stirred for 30 minutes to obtain three types of anode active material mixture slurry A (Si:G=5:1, 5:2, and 5:5). In addition, a high-shear mixer (22000 rpm) was used for stirring in the preparation of these anode active material mixture slurries.
[0090] [Table 1]
[0091] [Preparation of negative electrode active material mixture slurry 2] 0.7 g of porous silicon particles and graphene nanoplatelets (Nanografi, thickness 3 nm, average particle size 1.5 μm, specific surface area 800 m 2 0.7 g of 10 ...
[0092] [Preparation of negative electrode] For each of the three types of negative electrode active material mixture slurry A (Si:G = 5:1, 5:2 and 5:5) and slurry B (SiGNP), a negative electrode was prepared using a copper foil on which a single-layer graphene layer was formed by a CVD method, and a copper foil on which a single-layer graphene layer was not formed. For the copper foil on which a single-layer graphene layer was formed, the negative electrode active material mixture slurry was applied to the surface of the single-layer graphene layer so that the dry film thickness was 50 μm, and then dried in a thermostatic chamber at 80 ° C. for 6 hours, and then dried at 120 ° C. for 12 hours using a vacuum dryer to obtain a negative electrode. For the copper foil on which a single-layer graphene layer was not formed, the negative electrode active material mixture slurry was applied to the surface of the copper foil so that the dry film thickness was 50 μm, and then dried in a thermostatic chamber at 80 ° C. for 6 hours, and then dried at 120 ° C. for 12 hours using a vacuum dryer to obtain a negative electrode. The negative electrode prepared using the negative electrode active material mixture slurry A is referred to as "negative electrode A," and the negative electrode prepared using the negative electrode active material slurry B is referred to as "negative electrode B."
[0093] [Evaluation of charge / discharge cycle characteristics] For each of the negative electrodes obtained by the above procedure, a CR2032 half cell was assembled using lithium foil as a counter electrode, and connected to a battery charger (Hokuto Denko Corporation, product name HJ1001SD8) using a four-terminal method to evaluate the charge / discharge cycle characteristics. In the evaluation, charging was performed in constant current constant voltage (CCCV) mode, charging at a constant current until the voltage reached 0.01 V, and after the voltage reached 0.01 V, charging at a constant voltage of 0.01 V until the current value fell below the lower limit current. Discharging was performed in constant current (CC) mode, discharging at a constant current until the voltage reached 2 V. Since this is an evaluation of the negative electrode, the positive side of the battery charger was connected to the negative electrode of the battery, and the negative side was connected to the positive electrode of the battery. Therefore, unlike normal battery evaluation, the voltage decreases as charging progresses, and increases as discharging progresses. The current value was set to 0.05 C (minimum current 0.001 C) in the first cycle and 0.2 C (minimum current 0.004 C) from the second cycle onwards, with the theoretical capacity being 1 C. The charge retention rate was calculated based on the charge capacity in the second cycle.
[0094] FIG. 1 shows a plot of the charge retention rate versus cycle number for each negative electrode A (Si:G=5:1, 5:2, and 5:5) when a negative electrode A without CVD single-layer graphene formed on the current collector was used. As shown in FIG. 1, when any negative electrode A with Si:G=5:1, 5:2, or 5:5 was used, the charge capacity rapidly decreased at about 10 to 40 cycles, and the charge-discharge cycle characteristics were poor. However, with regard to the ratio of Si:G contained in the negative electrode, the charge-discharge cycle characteristics tended to improve as the mixture ratio of G (crushed graphite) increased.
[0095] FIG. 2 shows a plot of the charge retention rate versus the number of cycles for each negative electrode A (Si:G=5:1, 5:2, and 5:5) when a negative electrode A with CVD single-layer graphene formed on the current collector was used. As shown in FIG. 2, a significant improvement in charge-discharge cycle characteristics was observed compared to when a negative electrode A without CVD single-layer graphene formed on the current collector was used (FIG. 1). In addition, with regard to the ratio of Si:G contained in negative electrode A, as the mixture ratio of G (crushed graphite) increased, the charge-discharge cycle characteristics tended to improve, and the charge-discharge cycle was particularly good when Si:G=5:2 to 5:5.
[0096] Figure 3 shows a plot of charge retention versus cycle number when using anode B (SiGNPs) with CVD single-layer graphene formed on the current collector. For comparison, Figure 3 also shows a plot of anode A (Si:G=5:5) with CVD single-layer graphene formed. As shown in Figure 3, anode B using graphene nanoplatelets showed better cycle characteristics than anode A using crushed graphite, and the charge capacity retention at 101 cycles was much higher than that of anode A.
[0097] As described above, it can be understood that by using a composite of porous silicon particles and crushed graphene particles or graphene nanoplatelets as a negative electrode material and forming a graphene layer on the negative electrode current collector, a lithium ion secondary battery with excellent cycle characteristics can be obtained.
Claims
1. A negative electrode material for a lithium ion secondary battery, comprising a composite of crushed graphite particles or graphene nanoplatelets having an average particle size of 0.1 μm to 30 μm and porous silicon particles.
2. The mass ratio of the porous silicon particles (Si) to the crushed graphite particles or graphene nanoplatelets (G) is Si:G = 5:1 to 5:
5. The negative electrode material for lithium ion secondary batteries according to claim 1.
3. 2. The negative electrode material for a lithium ion secondary battery according to claim 1, wherein the porous silicon particles are surface-coated with the crushed graphite particles or the graphene nanoplatelets.
4. 2. The negative electrode material for a lithium ion secondary battery according to claim 1, wherein the crushed graphite particles contain graphene flakes.
5. A negative electrode for a lithium ion secondary battery comprising the negative electrode material for a lithium ion secondary battery according to any one of claims 1 to 4 on the graphene layer of a current collector having a graphene layer on its surface.
6. A lithium ion secondary battery comprising the negative electrode for lithium ion secondary batteries according to claim 5 as a negative electrode.
7. a dispersion step of subjecting a mixture of graphite or graphene nanoplatelets and a solvent to a treatment using an external force to crush and / or disperse the graphite or graphene nanoplatelets in the solvent to obtain a dispersion; a mixing step of mixing at least the dispersion liquid obtained in the dispersing step, porous silicon particles, a binder, and water to prepare a slurry of a negative electrode active material mixture.
8. The method for producing a negative electrode material for a lithium ion secondary battery according to claim 7, wherein the treatment by external force is ultrasonic treatment.
9. 8. The method for producing a negative electrode material for a lithium ion secondary battery according to claim 7, wherein the graphite is expanded graphite flakes.
10. A dispersion step of subjecting a mixture of graphene nanoplatelets, porous silicon particles, and a solvent to a treatment using an external force to obtain a dispersion in which the graphene nanoplatelets and the porous silicon particles are dispersed in the solvent; a mixing step of mixing at least the dispersion liquid obtained in the dispersing step, a binder, and water to prepare a slurry of a negative electrode active material mixture.
11. a graphene layer forming step of forming a single graphene layer on a surface of a current collector; a coating step of coating the slurry obtained by the method according to any one of claims 7 to 10 on the graphene layer of the current collector that has been subjected to the graphene layer forming step, and drying the slurry.
Citation Information
Patent Citations
Lithium ion secondary battery
JP2013073846A
Collector, electrode for electrochemical cell using the same, and electrochemical cell
JP2013140770A
Porous electrode active materials
JP2013538777A
Carbon material and production method of the same
JP2015044737A
Silicon-based composite negative electrode material for lithium ion secondary batteries, manufacturing method, and battery
JP2015118911A